ESCMID/EUCIC clinical practice guidelines on perioperative antibiotic prophylaxis in patients colonized by multidrug-resistant Gram-negative bacteria before surgery. (April 2023) - Righi, Elda; Mutters, Nico T.; Guirao, Xavier; del Toro, Maria Dolores; Eckmann, Christian; Friedrich, Alex W.; Giannella, Maddalena; Kluytmans, Jan; Presterl, Elisabeth; Christaki, Eirini; Cross, Elizabeth L.A.; Visentin, Alessandro; et al.
Abstract: Scope: The aim of the guidelines is to provide recommendations on perioperative antibiotic prophylaxis (PAP) in adult inpatients who are carriers of multidrug-resistant Gram-negative bacteria (MDR-GNB) before surgery. Methods: These evidence-based guidelines were developed after a systematic review of published studies on PAP targeting the following MDR-GNB: extended-spectrum cephalosporin-resistant Enterobacterales, carbapenem-resistant Enterobacterales (CRE), aminoglycoside-resistant Enterobacterales, fluoroquinolone-resistant Enterobacterales, cotrimoxazole-resistant Stenotrophomonas maltophilia, carbapenem-resistant Acinetobacter baumannii (CRAB), extremely drug-resistant Pseudomonas aeruginosa, colistin-resistant Gram-negative bacteria, and pan-drug-resistant Gram-negative bacteria. The critical outcomes were the occurrence of surgical site infections (SSIs) caused by any bacteria and/or by the colonizing MDR-GNB, and SSI-attributable mortality. Important outcomes included the occurrence of any type of postsurgical infectious complication, all-cause mortality, and adverse events of PAP, including development of resistance to targeted (culture-based) PAP after surgery and incidence of Clostridioides difficile infections. The last search of all databases was performed until April 30, 2022. The level of evidence and strength of each recommendation were defined according to the Grading of Recommendations Assessment, Development and Evaluation approach. Consensus of a multidisciplinary expert panel was reached for the final list of recommendations. Antimicrobial stewardship considerations were included in the recommendation development. Recommendations: The guideline panel reviewed the evidence, per bacteria, of the risk of SSIs in patients colonized with MDR-GNB before surgery and critically appraised the existing studies. Significant knowledge gaps were identified, and most questions were addressed by observational studies. Moderate to high risk of bias was identified in the retrieved studies, and the majority of the recommendations were supported by low level of evidence. The panel conditionally recommends rectal screening and targeted PAP for fluoroquinolone-resistant Enterobacterales before transrectal ultrasound-guided prostate biopsy and for extended-spectrum cephalosporin-resistant Enterobacterales in patients undergoing colorectal surgery and solid organ transplantation. Screening for CRE and CRAB is suggested before transplant surgery after assessment of the local epidemiology. Careful consideration of the laboratory workload and involvement of antimicrobial stewardship teams before implementing the screening procedures or performing changes in PAP are warranted. High-quality prospective studies to assess the impact of PAP among CRE and CRAB carriers performing high-risk surgeries are advocated. Future well-designed clinical trials should assess the effectiveness of targeted PAP, including the monitoring of MDR-GNB colonization through postoperative cultures using European Committee on Antimicrobial Susceptibility Testing clinical breakpoints.